Dampak Bencana Pada Pendidikan di Era Pasca Covid-19 : Tanggapan Kebijakan dan Strategi Ketahanan di Indonesia - Azka Murfiqoh (Tamilis Synex: Multidimensional Collaboration, 2025)
The COVID-19 pandemic has highlighted the vulnerabilities of education systems globally, particularly in disaster-prone countries like Indonesia. This study examines the multidimensional impacts of disasters on education in the post-pandemic era, analyzes government policies aimed at mitigating these impacts, and proposes strategies for building more resilient education systems. Using a qualitative literature review approach, the study draws on data from government reports, academic publications, and international organizations. The findings reveal that disasters exacerbate existing challenges, including infrastructure damage, psychosocial trauma, and the digital divide. Government initiatives such as the Disaster-Safe Education Unit Program (SPAB) and Disaster-Resilient Education are important steps, but their implementation remains uneven. The study concludes that a comprehensive approach integrating disaster risk reduction into the curriculum, enhancing teacher capacity, establishing emergency funding mechanisms, and prioritizing mental health support is crucial for creating education systems that can withstand future crises.